Hubungan Antara Status Gizi Dengan Prestasi Belajar Anak Sekolah Dasar Di Sdn Ngringin Depok Sleman Yogyakarta - Adrianus Maku; Ni Ketut Mendri; Aan Devianto (Poltekkes Kemenkes Yogyakarta, 2018)
Nutritional status is one of the factors that can affect the learning achievement in addition to other factors, such as family factors, environment, motivation, and facilities and infrastructure obtained in school. The low nutritional status of children will have a negative impact on improving the quality of human resources. Malnutrition is closely related to the achievement of low academic achievement. Objective: To find out the correlation between nutritional status with elementary school student achievement in SDN Naringin, Depok, Sleman, Yogyakarta. Method: Based on the result of the research, nutritional status was more than 8 respondents (13,3%), good nutrition status was 39 respondent (65,0%), nutrient status was less 13 respondent (21,7%). While the learning achievement of children is very good as much as 8 respondents (13.3%), learning achievement is good as 28 respondents (46.7%), learning achievement is quite as much as 15 respondents (25.0%) and less learning achievement as much as 9 respondents (15.0%). Conclusion: There is a significant correlation between nutritional status with primary school student achievement in SDN Ngringin, Depok, Sleman, Yogyakarta with p-value 0,00 (p< 0,05). The relationship between nutritional status with the achievement of elementary school students in SDN Ngringin, Depok, Sleman, Yogyakarta stated tightly that is equal to 0.756.